Short-term Overreaction of the Indonesian Islamic Stock Market to Specific Events during the Covid-19 Pandemic - Rosmala, Novia; Irfany, Mohammad Iqbal; Camara, Bumi; Haq, Daffa Aqomal (Ekonomi Islam Indonesia, 2024)
The COVID-19 pandemic is a rare and unexpected occurrence. Everyone has felt the global economic impact of the health crisis, including the Indonesian Islamic stock market. The shock in the Islamic stock markets has created uncertainty and a shift in investor behavior, potentially leading to an overreaction abnormality. The aim of this research is to look into a phenomenon in Indonesia's Islamic stock market. Analytical methods include the event study approach and cross-sectional regression. This study discovered that Joe Biden's election as President of the United States during the COVID-19 pandemic (Event 8) and the increase in daily COVID-19 deaths (Event 11) overreacted to the winner category stocks using the Jakarta Islamic Index (JII). A component that drives such overreactions is market capitalisation, which has a substantial influence on it. Furthermore, trading volumes influenced overreaction significantly.